2010
DOI: 10.1371/journal.pone.0015743
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin 2 Is the Predominant γ-Secretase in Microglia and Modulates Cytokine Release

Abstract: Presenilin 1 (PS1) and Presenilin 2 (PS2) are the enzymatic component of the γ-secretase complex that cleaves amyloid precursor protein (APP) to release amyloid beta (Aβ) peptide. PS deficiency in mice results in neuroinflammation and neurodegeneration in the absence of accumulated Aβ. We hypothesize that PS influences neuroinflammation through its γ-secretase action in CNS innate immune cells. We exposed primary murine microglia to a pharmacological γ-secretase inhibitor which resulted in exaggerated release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 70 publications
2
49
1
Order By: Relevance
“…In corroboration of our findings, recent reports have shown that PS2 ␥-secretase cleaved more APP than PS1 ␥-secretase in microglia cells, regardless of the presence of PS1 (31). Thus, when studying ␥-secretase activity, we should consider the concentration of PS in the active ␥-secretase complex, which may aid in clarifying the pathogenesis of FAD caused by PS loss-of-function FAD mutations.…”
Section: Discussionsupporting
confidence: 90%
“…In corroboration of our findings, recent reports have shown that PS2 ␥-secretase cleaved more APP than PS1 ␥-secretase in microglia cells, regardless of the presence of PS1 (31). Thus, when studying ␥-secretase activity, we should consider the concentration of PS in the active ␥-secretase complex, which may aid in clarifying the pathogenesis of FAD caused by PS loss-of-function FAD mutations.…”
Section: Discussionsupporting
confidence: 90%
“…PS1 and PS2 have overlapping functions and are required for development and adult brain functions (Wines-Samuelson and Shen, 2005;Ho and Shen, 2011). The presenilin-1 (PS1) knock-out (KO) mice show perinatal lethality and impaired neural development (Shen et al, 1997;Handler et al, 2000;WinesSamuelson et al, 2005), whereas PS2 KO mice have little detectable phenotypes (Steiner et al, 1999), but PS1/2 double KO mice exhibit more severe phenotypes and die at embryonic day 9 (Donoviel et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…PSEN mutations confer partial loss of its presenilin function, and some mutations result in complete loss of its activity (Levitan et al, 1996;Song et al, 1999;Moehlmann et al, 2002;Seidner et al, 2006;Heilig et al, 2010). These findings together with striking age-dependent neurodegeneration observed in PS cDKO mice suggested that PSEN mutations might lead to AD as a result of partial loss of PS essential functions (Shen and Kelleher, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Brain samples from embryonic day 15 Psen1, and postnatal day 11 Psen2 KO mice were provided by Dr. Strooper (13) and Jayadev et al (26), respectively.…”
Section: Mouse Strains-tg-a246epsen1mentioning
confidence: 99%